The factors that inluence consumer determinations to purchase organic vegetables: Case study at TESCO Kota Bharu / Mohd Hafiz Ismail - Ismail, Mohd Hafiz (2012)
Malaysia consumers have become more health conscious and consequently organic food consumption has increased recently. Even though the market of organic product is growing, still the demand on organic food is unstable at market place. This research studies the factor that determinations of consumer to purchase organic vegetables. 50questionnaires were collection from the respondents in Tesco Kota Bharu. The results have discovered that attitude, perception, health and knowledge are main important factors that can influence consumer purchase intention on organic vegetables. These finding can be helpful for marketing managers in order to develop the most suitable strategy to gain higher level of market share.